THE CORRELATION BETWEEN SOPHOMORES’ AUTONOMOUS LEARNING OF WRITING AND THEIR WRITING ABILITY - Muhammad ilham; rizki fiprinita (Indonesian Journal of Integrated English Language Teaching, 2018)
Being autonomous in language learning is essentially necessary, particularly for EFL students having willingness to enhance their ability in scope of writing, and this issue had researcher intended to regard as research subject, and more to find out and examine its correlation in term of research variables as well. To this end, the selected samples were made to fill a five-point scale questionnaire purposed to discover their autonomous learning of writing, and to take narrative writing test. The correlations were examined through Pearson product-moment correlation coefficient (r) with no exception to also determine the strength of its correlation. Moreover, coefficient of determination was computed to see the extent to which sophomores’ autonomous learning of writing contributes their writing ability. Thus, this research applied a quantitative method design. Pearson r demonstrates that there is a strong significant correlation between sophomores’ autonomous learning of writing and their writing ability (r value > r table, 0.769 > 5%). The coefficient of determination also reveals that sophomores’ autonomous learning of writing has affective contribution to their writing ability at 59%. Based on the findings, some recommendations have been made.